Comparative Analysis of Disaster Management Strategies in India and Indonesia - Handore, Komal Raosaheb; Patil, Neha; Dangle, Mayuri (Indonesian Journal of Geography, 2025)
The present research compares and contrasts the legal institutional framework of the disaster management system between India and Indonesia. The primary objective of this research is to assess the efficiency and effectiveness of the disaster management frameworks of both countries, identifying their strengths and weaknesses, and suggesting potential improvements to the existing system. The introduction part of the study presents an overview of disaster management efforts worldwide and in Asia, followed by a literature review of several studies conducted to evaluate the efficiency and effectiveness of disaster management frameworks in various countries. The second part of the study presents a holistic overview of the disaster management systems in India and Indonesia, including disaster profiles, disaster risk and vulnerability, disaster preparedness, response, mitigation, and recovery strategies, as well as the legal and institutional frameworks of both countries. The research reveals that both nations should move beyond merely managing the risk. They should associate and integrate climate change adaptation strategies with disaster risk reduction. The research work set the stage for a deeper exploration of the complexities, innovations, and collaborations necessary to navigate the dynamic landscape of disaster risk and climate change adaptation in India and Indonesia.